Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja serta Implikasinya pada Motivasi Personel di POLRI (Studi Kasus di Bagian Perencanaan Administrasi Staf SDM) - Budiyanto, Fajar; Junaidi, Junaidi; Kamaruddin, Kamaruddin (Singkite Journal, 2025)
The purpose of the study was to determine the contribution of work environment factors and member discipline in improving performance that has implications for work motivation. case study on POLRI Aceh personnel. Using an associative method with a quantitative approach with data analysis techniques through the path model. The sample in this study was personnel of the Human Resources Staff Planning Administration Section of the Police totaling 76 people. The results of the study showed that 1) There is a causal relationship between work environment variables and work discipline with a degree of 0.699. 2) There is a direct and indirect influence of the work environment on performance, through the work discipline variable, of 45.33%. 3) There is a direct and indirect influence of work discipline on performance, through the work environment variable, of 30.72%. 4) Simultaneously, the work environment and work discipline have a significant effect and contribute 46.7% to personnel performance. 5) There is a direct and indirect influence of the work environment on motivation, through the work discipline variable, of 30.36%. 6) There is a direct and indirect influence of work discipline on motivation, through the work environment variable of 28.59%. 7) Simultaneously, the work environment and work discipline provide a positive contribution to work motivation of 40.1%. 8) The total influence of the work environment and work discipline on work loyalty, through the performance variable, namely: 7% + 7.04%, is obtained at 14.04%.